2018
DOI: 10.1165/rcmb.2017-0286oc
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between EZH2 and G9a RegulatesCXCL10Gene Repression in Idiopathic Pulmonary Fibrosis

Abstract: Selective repression of the antifibrotic gene CXCL10 contributes to tissue remodeling in idiopathic pulmonary fibrosis (IPF). We have previously reported that histone deacetylation and histone H3 lysine 9 (H3K9) methylation are involved in CXCL10 repression. In this study, we explored the role of H3K27 methylation and the interplay between the two histone lysine methyltransferases enhancer of zest homolog 2 (EZH2) and G9a in CXCL10 repression in IPF. By applying chromatin immunoprecipitation, Re-ChIP, and prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…Supporting the utility of our screen, several enzymes already reported to be important in fibroblast biology and fibrosis, such as bromodomain-containing proteins (e.g. BRD4) (Tang et al, 2013) and EZH2 (Coward et al, 2018;Xiao et al, 2016) were identified. We chose to focus on pracinostat because it was most effective in our primary assay outcome, and because HDAC inhibition has proven effective in fibrosis models (Barter et al, 2010;Bombardo et al, 2018;Conforti et al, 2017;Glenisson et al, 2007;Guo et al, 2009;Kang et al, 2017;Khalil et al, 2015;Kim et al, 2018;Ota et al, 2015) but its anti-fibrotic effects remain poorly understood.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Supporting the utility of our screen, several enzymes already reported to be important in fibroblast biology and fibrosis, such as bromodomain-containing proteins (e.g. BRD4) (Tang et al, 2013) and EZH2 (Coward et al, 2018;Xiao et al, 2016) were identified. We chose to focus on pracinostat because it was most effective in our primary assay outcome, and because HDAC inhibition has proven effective in fibrosis models (Barter et al, 2010;Bombardo et al, 2018;Conforti et al, 2017;Glenisson et al, 2007;Guo et al, 2009;Kang et al, 2017;Khalil et al, 2015;Kim et al, 2018;Ota et al, 2015) but its anti-fibrotic effects remain poorly understood.…”
Section: Discussionsupporting
confidence: 61%
“…Variations in the epigenome have been shown to accompany fibrosis disease progression in multiple tissues (Coward et al, 2009;Page and Mann, 2015;Yang and Schwartz, 2015). Specifically, diseased lung fibroblasts have been shown to exhibit causative alterations in DNA methylation, histone acetylation and micro (mi)RNAs when compared to their non-diseased counterparts (Coward et al, 2018(Coward et al, , 2014(Coward et al, , 2009Huang et al, 2014;Khalil et al, 2015;Lino Cardenas et al, 2013;Liu et al, 2010;Miao et al, 2018;Sanders et al, 2012Sanders et al, , 2017Tang et al, 2013;Xiao et al, 2016;Yang et al, 2014Yang et al, , 2013. Recently, we identified several epigenetic regulators in an siRNA screen of fibroblast activation (Oh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the protein expression results (Figure 4B ), ethanol exposure at P7 significantly ( F (3,33) = 44, p < 0.01; two-way ANOVA with Bonferroni’s post hoc ) reduced Arc mRNA levels in the adult HP (Figure 4C ), and pre-administration of Q-VD-OPh at P7 rescued it, suggesting that long-lasting Arc expression deficits are transcriptionally regulated. It is well established that MeCP2 silences gene transcription by recruiting the histone deacetylase (HDAC, which removes acetyl groups from histones; Nan et al, 1997 , 1998 ) or G9a (adds methyl groups to histones; Fuks et al, 2003 ; Coward et al, 2017 ) repressive molecular machineries. Additionally, reduced pCREB levels can impair recruitment of the CREB binding protein, CBP (intrinsic histone acetyl transferase activity, HAT adds acetyl groups to histones) to gene promoters (Lonze and Ginty, 2002 ; Lubin et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…As we determined that both matrix stiffness and TGF-β are important drivers of H3K9 methylation in lung fibroblasts, we reasoned that H3K9me mark deposition by a histone methyltransferase may be critical to promote fibroblast activation in response to biomechanical or biochemical stimuli. We therefore cultured normal human lung fibroblasts on soft or stiff substrates for 24 hours in presence or absence of a small-molecule inhibitor (BIX01294) that specifically blocks the enzymatic activity the G9a histone methyltransferase (50), which is known to both bind CBX5 (48) and promote H3K9 methylation (28) and has recently been implicated in IPF fibroblast genetic repression (22,51). BIX01294 treatment prevented matrix stiffness-induced αSMA upregulation and reduced the levels of H3K9 methylation in lung fibroblasts ( Figure 2C), suggesting that G9a-induced H3K9 methylation is required to promote fibroblast activation in response to biomechanical stimuli.…”
Section: Inhibition Of the Histone Methyltransferase G9a Blocks Biochmentioning
confidence: 99%
“…Altered epigenetic programs in diseased lung fibroblasts are known to contribute to idiopathic pulmonary fibrosis (IPF) (11,16). While much attention has been given to the epigenetic activation of profibrotic gene expression during lung fibrosis development (11,17,18), only recently epigenetic repression of antifibrotic genes has become appreciated as a potential mechanism that prevents the return of activated lung fibroblasts to a quiescent state (19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%